Speech by Collettivo La Boétie - November 18th, 2020 (Balthazar, 2022)
Transcription of Collettivo La Boétie's speech during the cycle of conferences on Civil disobedience 2020-2021.
Keywords: voluntary servitude; freedom; friendship